Balanced nutrition education as an effort to prevent stunting in toddlers - Hatijar Hatijar; Ari Setiawati; Lamria Situmeang; Indrawati Aris Tyarini; Sitti Zakiyyah Putri; Lina Yunita (Jurnal Pengabdian Masyarakat Edukasi Indonesia, 2025)
Stunting is one of the health problems that is still highly prevalent in Indonesia, especially in toddlers. This condition has a long-term impact on children's physical growth, cognitive development, and productivity in the future. One of the main factors causing stunting is the ignorance of parents or caregivers about the importance of balanced nutrition in the child's growth period. This community service activity aims to increase public knowledge and awareness, especially among mothers with toddlers, about the importance of providing balanced nutrition to prevent stunting. The method used in this activity is education through counseling, interactive discussions, and distribution of educational media through leaflets and posters. The activity was conducted at the Posyandu and involved health cadres and nutritionists. The evaluation results showed an increase in participants' knowledge by 75% based on the pre-test and post-test. This activity shows that direct and contextual balanced nutrition education can effectively prevent stunting in toddlers